The Potential Clinical Properties of Magnesium - Crisponi, Guido; Nurchi, Valeria M.; Cappai, Rosita; Zoroddu, Maria Antonietta; Gerosa, Clara; Piras, Monica; Faa, Gavino; Fanni, Daniela (Current Medicinal Chemistry, 2021)
A significant percentage of costs in pharmaceutical markets is devoted to supplements due to the confidence of consumers in the beneficial effects of these products. Magnesium is one of the supplements with enduring and increasing popularity. According to what is reported online, this metal ion can cure or prevent almost all kinds of diseases. This review aims at illustrating a series of scientifically demonstrated cases in which magnesium was used in clinical practice. Except for its ordinary use as antacid and laxative, other ascertained uses, reported in scientific literature, consist of helping to treat several diseases such as nocturnal leg cramps, pre-eclampsia, diabetes, depression, Parkinson’s and Alzheimer’s disease, hypertension, some types of arrhythmias, asthma, migraine headaches, epilepsy, cerebral haemorrhage, and stroke. However, many of these promising uses of magnesium require further studies to define the involved molecular mechanisms which should help establishing its uses in relation to the prolonged use of supplements.
Keywords: depression